Seeing Muslim Men and Women Hermeneutically: A Liberal-Feminist Study on Amina Wadud’s Qur’an Exegesis - Dahlia Kartika Ariesita; Galant Nanta Adhitya (Universitas Gadjah Mada, 2023)
Gender inequality became one of the important issues in the US as it intersects with other societal aspects, one of which is religion. In the last century, the US has seen a fast-growing number of believers in Islam, despite its unequal practices based on gender. American Muslim women are not only treated differently due to religious beliefs but also to racial backgrounds. The emergence of Amina Wadud, a female Imam with an African-American background, brings new thoughts on the position of women in Islam. Employing the Post-Nationalist approach combined with Rosemarie Tong’s liberal feminism theory, this article analyzes Wadud’s Qur’an and Women: Re-reading the Sacred Text from a Woman’s Perspective to reveal her thinking in becoming a female Imam in the US, as well as her fights against injustices towards Muslim women. It finds that her background as an African-American woman, a second class in American society, pushes her to put women’s rights in Islam forward, which are not consistent in the Qur’an. She re-interprets it with the hermeneutic method, putting women and men in the same position. While her pro-faith determination for equality drives her to overcome the rejection from the American Muslim community when she became an imam in a mixed congregation of Friday prayers.